Large‐scale flow vortices following a magnetospheric sudden impulse. Issue 6 (7th June 2013) - Samsonov, A. A.; Sibeck, D. G.
Abstract : [1] Global MHD simulations predict the generation of flow vortices on the magnetospheric flanks near the equatorial plane after the impact of solar wind dynamic pressure pulses on the magnetosphere. These vortices are associated with field‐aligned currents, having similar senses to those responsible for the main impulse, i.e., the second impulse of the well‐known sudden impulse variations at high geomagnetic latitudes. We investigate the evolution of the vortices and show that they result from the interaction of a fast MHD wave and the inner (near‐Earth) boundary of numerical models. Near the inner boundary, the Ampere force decelerates plasma flow resulting in two closely related phenomena: the generation of flow vortices and the launch of a reflected fast wave moving sunward. The vortices propagate antisunward and split into several parts during several minutes. The reflected wave interacts with the magnetopause and bow shock and changes its velocity. The interaction between the reflected wave and bow shock results in two new discontinuities moving earthward through the magnetosheath. The first is either a very weak fast rarefaction wave or a weak fast shock, and the second is either a tangential discontinuity or a compound discontinuity with a decrease of the density and magnetic field and an increase of the temperature. We speculate that the inner boundary in simulations may correspond to either the plasmasphere or ionosphere. Key Points: Vortices following a sudden impulse are generated near inner numerical boundary. Vortex generation and fast wave reflection are two closely related phenomena. Vortices result in field aligned currents responsible for main impulse in SI.